Achievements and Prospects of Intercultural Communication (International Journal of Scientific Trends, 2025)
This article underscores the field of study and practice encompasses the ways in which people from different cultural backgrounds communicate, understand, and relate to one another. As societies become more interconnected through technology, migration, and international trade, the achievements and prospects of intercultural communication are more relevant than ever. In an increasingly globalized world, intercultural communication has emerged as a vital component of effective interaction among diverse cultures.